The role of infaq in the Qur'an: A gender review of women's generosity - Muchtar, Evan Hamzah; Utama, Mohamad Maulidin Alif (Pusat Studi Gender dan Anak, 2024)
Infaq is currently very interesting and needs to be discussed and developed. Though it is not gender-specific, infaq is not just for men; women play a crucial role in it. This study examines how women perform infaq and infaq in the Koran. A qualitative approach was used in this study, using a research library. This study demonstrates the value of charity in human life; women are acknowledged as active contributors to charity, and there are no gender-based barriers to charitable giving. It is hoped that more women will be motivated to give back if they comprehend this perspective. Their participation has the potential to improve society and fortify social networks. Therefore, women's infaq enhances their spiritual experience and strengthens social bonds within the community.